Restoring the balance a Middle East strategy for the next president - Haass, Richard (Brookings Institution Press, 2008)
"Experts from the Brookings Saban Center and Council on Foreign Relations propose a new, nonpartisan strategy drawing on the lessons of past failures to address short-term and long-term challenges to U.S. interests. Issues and policy recommendations cover the Arab-Israeli conflict, counterterrorism, Iran, Iraq, political and economic development, and nuclear proliferation"--Provided by publisher